The Origins and Evolution of Sentencing Guidelines - Young, Warren; King, Andrea (Sentencing Guidelines, 2013)
This chapter compares and contrasts the sentencing guidelines in England and Wales with the corresponding sentencing guidelines developed but not yet implemented in New Zealand. In this essay, the objectives of a sentencing guidelines system are explored. The text explores what is required to achieve these objectives and considers on this basis how successful each jurisdiction’s scheme is likely to be. We conclude that the New Zealand model has many more of the ingredients for success than the model in England and Wales.